2018
DOI: 10.2116/analsci.34.243
|View full text |Cite
|
Sign up to set email alerts
|

Droplet-counting Microtitration System for Precise On-site Analysis

Abstract: A new microtitration system based on the counting of titrant droplets has been developed for precise on-site analysis. The dropping rate was controlled by inserting a capillary tube as a flow resistance in a laboratory-made micropipette. The error of titration was 3% in a simulated titration with 20 droplets. The pre-addition of a titrant was proposed for precise titration within an error of 0.5%. The analytical performances were evaluated for chelate titration, redox titration and acid-base titration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Kawakubo et al designed a microtitration system based on the counting of titrant droplets for precise on-site analysis. 10 On-site measurements of tap water collected in an office kitchen were performed, and the analytical results agreed with those of conventional titration with an error of 3%.…”
mentioning
confidence: 62%
“…Kawakubo et al designed a microtitration system based on the counting of titrant droplets for precise on-site analysis. 10 On-site measurements of tap water collected in an office kitchen were performed, and the analytical results agreed with those of conventional titration with an error of 3%.…”
mentioning
confidence: 62%
“…Sample sizes in the microgram range and solution volumes of 10-100 µL were used. Kawakubo et al developed a portable microtitration system for field applications based on titrant droplet counting technique [9] . They used a home-made dropper-type micro-burette and a 25-mL sample vial to house the 2-mL sample solution.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, some studies on micro-batchwise titration have been reported. 4,5 This study aims to develop an alternative and cost-effective approach to make the reagent reusable in conventional batch titration towards a green chemical analysis. Moreover, natural reagents were also of interest as alternatives to commercial synthesized chemicals.…”
Section: Introductionmentioning
confidence: 99%